Method of forming composite plated film with its outermost layer made of fluorocarbon resin, and substrate coated with composite plated film with its outermost layer made of fluorocarbon resin, formed by the forming method

A five-step process forms a fluororesin outermost layer on substrate materials, addressing the insufficient acid resistance of composite plating films by ensuring complete coverage and adhesion, thereby preventing corrosion from acidic substances.

JP2025012530APending Publication Date: 2025-01-24KANTO GAKUIN SCHOOL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023115420
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing methods for improving the acid resistance of substrate materials used in semiconductor manufacturing, such as those made of metal or resin materials, are insufficient in preventing corrosion from acidic substances like hydrofluoric acid and sulfuric acid, especially when a composite plating film with a fluororesin layer is used, as they often result in mechanical rigidity issues and incomplete coverage.

Method used

A method involving five steps: pretreatment of the substrate, formation of a metal plating film, creation of a composite plating film with a low concentration of fluororesin, formation of a composite plating film with a high concentration of fluororesin, and finally heat-treating the substrate to form an outermost layer of fluororesin, ensuring adhesion and complete coverage.

Benefits of technology

The method provides a substrate material with a fluororesin outermost layer that exhibits no corrosion potential when exposed to acidic substances, enhancing acid resistance without compromising mechanical rigidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012530000001_ABST
    Figure 2025012530000001_ABST
Patent Text Reader

Abstract

To provide a method of forming a composite plated film with its outermost layer made of a fluorocarbon resin, for imparting acid resistance to the substrate.SOLUTION: The invention according to the present application employs a method of forming a composite plated film with its outermost layer made of a fluorocarbon resin, the method comprising the following steps of: a step 1 of subjecting the substrate to a pretreatment including defatting and water-washing the substrate; a step 2 of forming a metal plated film on the substrate having been subjected to the pretreatment; a step 3 of forming a composite plated film including a fluorocarbon resin in a low concentration on the substrate coated with the metal plated film, in a plating bath being agitated; a step 4 of forming a composite plated film including the fluorocarbon resin in a high concentration on the substrate coated with the composite plated film including the fluorocarbon resin in a low concentration, in a plating bath being agitated; and a step 5 of subjecting the substrate coated with a composite plating film including the fluorocarbon resin in a high concentration to a heat treatment to form the outermost layer made of the fluorocarbon resin.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention of the present application relates to a method for forming a composite plating film having an outermost layer made of a fluororesin, in order to impart acid resistance to a substrate material made of a metal material or a resin material such as a polyimide resin, such that the substrate material is not corroded even when the substrate comes into contact with acidic substances such as hydrofluoric acid, sulfuric acid, and hydrochloric acid, and to a substrate material with a composite plating film formed by this method, the outermost layer of which is made of a fluororesin. [Background technology]

[0002] Conventionally, in semiconductor manufacturing processes, various concentrations of acidic aqueous solutions such as hydrofluoric acid, sulfuric acid, and hydrochloric acid, as well as acidic gases, are used. Therefore, jigs and various devices used in semiconductor manufacturing processes are required to be acid-resistant so that there is no risk of the surface corroding even when they come into contact with these substances. Here, fluororesins are widely used as acid-resistant substances in semiconductor manufacturing processes. However, when jigs and various devices are manufactured from fluororesins, the mechanical rigidity may be insufficient.

[0003] Therefore, a technique has been studied in which a composite plating film made of a fluororesin and a metal such as nickel is formed on the surface of a metal material having superior mechanical rigidity to fluororesin, or a resin material such as polyimide resin that is widely used in the semiconductor field, to improve the acid resistance of the substrate material made of the metal material or resin material. However, a composite plating film having such a configuration does not have the effect of significantly improving the acid resistance of the substrate material, because the metal such as nickel is exposed on a part of the surface.

[0004] On the other hand, Patent Document 1 discloses a technique for improving the water repellency of a substrate material by forming a composite plating film as described above on the surface of the substrate material, performing a heat treatment, and increasing the fluororesin content in the outermost surface of the composite plating film to approach 100 vol. %. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-217691 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the technology disclosed in Patent Document 1 is intended to improve the water repellency of the substrate material, and is insufficient in improving the acid resistance of the substrate material. Therefore, the market continues to demand a technology for improving the acid resistance of substrate materials made of metal materials and resin materials such as polyimide resin. [Means for solving the problem]

[0007] A. Method for forming composite plating film in which the outermost layer is a fluororesin The invention of the present application is a method for forming a composite plating film having an outermost layer made of a fluororesin for imparting acid resistance to a substrate material made of a metal or resin material, and is characterized by comprising the following steps 1 to 5.

[0008] Step 1: The substrate material is pretreated, including degreasing and rinsing. Step 2: A metal plating film is formed on the pretreated substrate material. Step 3: A composite plating film containing a low concentration of fluororesin is formed on the substrate material with the metal plating film while the plating bath is stirred. Step 4: A composite plating film containing a high concentration of fluororesin is formed on the substrate material with the composite plating film containing the low concentration of fluororesin while stirring the plating bath. Step 5: The substrate material with the composite plating film containing a high concentration of the fluororesin is subjected to a heat treatment to form an outermost layer made of fluororesin.

[0009] In the invention related to the present application, the substrate material is preferably any one of copper, aluminum, iron, stainless steel, and polyimide resin.

[0010] In the invention related to the present application, the fluororesin is preferably a polytetrafluoroethylene resin or a perfluoroalkoxyalkane resin.

[0011] In the invention according to the present application, the metal plating film formed in step 2 is preferably made of nickel or a nickel alloy.

[0012] In the invention related to the present application, the composite plating film formed in step 3 preferably contains 5% by mass to 25% by mass of a fluororesin.

[0013] In the invention related to the present application, the composite plating film formed in step 4 preferably contains 30% by mass to 65% by mass of a fluororesin.

[0014] B. Substrate material with composite plating film, the outermost layer of which is fluororesin The invention of the present application is a substrate material with a composite plating film having an outermost layer made of a fluororesin, formed by the method of forming a composite plating film in which the outermost layer is made of a fluororesin, as described above, and is characterized in that when a corrosion potential measurement is performed using any one of hydrofluoric acid, sulfuric acid, and hydrochloric acid as an electrolyte, the substrate material does not exhibit a corrosion potential for the electrolyte. Effect of the Invention

[0015] According to the invention of the present application, it is possible to impart acid resistance to a substrate material made of a metal material or a resin material such as a polyimide resin, such that there is no risk of corrosion even when the substrate comes into contact with an acidic substance such as hydrofluoric acid, sulfuric acid, or hydrochloric acid. [Brief description of the drawings]

[0016] [Figure 1] 1A and 1B are field emission scanning electron microscope images of an example according to the present application. [Diagram 2] 1 is a graph showing the results of measuring corrosion potential in an example according to the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] A. Method for forming composite plating film in which the outermost layer is a fluororesin The present invention relates to a method for forming a composite plating film having an outermost layer made of a fluororesin, which is characterized by comprising the following steps 1 to 5. By satisfying the requirements, the present invention can impart acid resistance to a substrate material made of a metal material or a resin material such as a polyimide resin, such that the substrate material is not corroded even when it comes into contact with an acidic substance such as hydrofluoric acid, sulfuric acid, or hydrochloric acid. Each step will be described below.

[0018] Step 1: The substrate material is pretreated, including degreasing and rinsing.

[0019] The substrate material of the invention according to the present application is a metal material or a resin material. There is no particular limitation on the type of metal material, and copper, aluminum, iron, stainless steel, etc. can be used. The resin material may be any material having a heat resistance of 400°C or higher, such as polyimide resin. This substrate material is pretreated by a conventional method including degreasing and washing with water. Specifically, for example, when a metal material is used as the substrate material, alkaline immersion degreasing, alkaline electrolytic degreasing, and acid immersion (also referred to as "acid activation") may be performed in this order, followed by washing with water. When a resin material is used as the substrate material, alkaline immersion degreasing, conditioning treatment, catalyst application treatment, acid immersion, catalyst application treatment again, and acid immersion again may be performed in this order, followed by washing with water.

[0020] Step 2: A metal plating film is formed on the pretreated substrate material.

[0021] In this step 2, a metal plating film is formed on the surface of the substrate material pretreated in the above step 1 as a base layer of the composite plating film described later. Here, the technical idea of ​​the invention according to the present application will be explained. In order to impart acid resistance to a substrate material made of a metal material or a resin material such as a polyimide resin, which is not likely to corrode even when it comes into contact with acidic substances such as hydrofluoric acid, sulfuric acid, and hydrochloric acid, a "composite plating film (a plating film mainly composed of a fluororesin and a metal)" whose outermost layer is a fluororesin may be formed on the surface of the substrate material. In order to form a composite plating film whose outermost layer is a fluororesin, a composite plating film containing a relatively high concentration of fluororesin is formed, and then the composite plating film is heat-treated to dissolve part of the fluororesin in the film, thereby forming an outermost layer made of fluororesin. However, if a composite plating film containing a fluororesin is formed on the surface of the substrate material without providing an underlayer, the adhesion to the substrate material surface is low, and there is a risk that the composite plating film will peel off from the substrate material surface. Therefore, in this step 2, it is necessary to form a metal plating film as a base layer.

[0022] As a method for forming the metal plating film in step 2, for example, when a metal material is used as the substrate material, an electroplating method or an electroless plating method may be adopted. When a resin material such as a polyimide resin is used as the substrate material, an electroless plating method may be adopted. The composition of the plating bath and the plating conditions may be appropriately determined depending on the type of substrate material, etc.

[0023] The metal plating film formed in step 2 is preferably nickel or a nickel alloy such as nickel-phosphorus, because nickel or a nickel alloy such as nickel-phosphorus can be formed relatively easily with good adhesion on the surface of a substrate material made of a metal material or a resin material by an electroplating method or an electroless plating method.

[0024] Step 3: A composite plating film containing a low concentration of fluororesin is formed on the substrate material with the metal plating film while the plating bath is stirred.

[0025] In this step 3, a composite plating film containing a relatively low concentration of fluororesin is formed as an intermediate layer on the surface of the metal plating film formed in the above-mentioned step 2. If a composite plating film containing a relatively high concentration of fluororesin is formed directly on the surface of the metal plating film, which is the base layer, without forming an intermediate layer, the adhesion to the metal plating film surface is low and there is a risk of peeling. Therefore, in this step 3, it is necessary to form a composite plating film containing a relatively low concentration of fluororesin as an intermediate layer.

[0026] Furthermore, there is no particular limitation on the type of fluororesin, and polytetrafluoroethylene (PTFE) resin, perfluoroalkoxyalkane (PFA) resin, etc., which are relatively inexpensive and easily available, can be used.

[0027] Here, the composite plating film formed in step 3 preferably contains 5% to 25% by mass of fluororesin. If the fluororesin content in the composite plating film formed in step 3 is less than 5% by mass, the adhesion of the composite plating film containing a relatively high concentration of fluororesin formed in the next step will be low and there is a risk of peeling, which is not preferred. On the other hand, if the fluororesin content in the composite plating film formed in step 3 exceeds 25% by mass, the adhesion to the metal plating film, which is the underlayer, will tend to be low, which is not preferred.

[0028] In the present step 3, the method for forming the composite plating film containing a low concentration of fluororesin is to mix a plating bath for precipitating a metal having the same composition as the underlayer formed in the above step 2 with a dispersion of fluororesin particles, and while stirring the mixture at a relatively slow speed with a stirrer, a composite plating film is formed by codeposition with the metal by electroplating or electroless plating. Specifically, for example, a composite plating film made of fluororesin and nickel may be formed on the surface of the above underlayer by electroplating using an electroplating solution consisting of an aqueous solution of nickel sulfamate tetrahydrate with a concentration of 600 g / L to 900 g / L, an aqueous solution of boric acid with a concentration of 40 g / L, and a dispersion of polytetrafluoroethylene resin with a concentration of 50 g / L to 200 g / L, while stirring the mixture with a stirrer at a speed of 2 cm / sec to 10 cm / sec. Here, if the composite plating film in step 3 is formed on the surface of the base layer without stirring, the fluororesin particles will partially settle, making it impossible to obtain a homogeneous composite plating film with good reproducibility, and the adhesion of the composite plating film containing a relatively high concentration of fluororesin to be formed in the next step will tend to decrease, which is not preferable.

[0029] Step 4: A composite plating film containing a high concentration of fluororesin is formed on the substrate material with a metal plating film containing a low concentration of fluororesin while stirring the plating bath.

[0030] In this step 4, a composite plating film containing a relatively high concentration of fluororesin is formed on the surface of the composite plating film containing a relatively low concentration of fluororesin formed in the above-mentioned step 3. As described above, after the composite plating film containing a relatively high concentration of fluororesin is formed on the surface of the substrate material, an outermost layer made of fluororesin is formed by performing a heat treatment. As a result, it is possible to impart acid resistance to a substrate material made of a metal material or a resin material such as a polyimide resin, such that there is no risk of corrosion even when the substrate material comes into contact with an acidic substance such as hydrofluoric acid, sulfuric acid, or hydrochloric acid.

[0031] Here, the composite plating film formed in step 4 preferably contains 30% to 65% by mass of fluororesin. If the content of fluororesin in the composite plating film formed in step 4 is less than 30% by mass, an outermost layer consisting of only fluororesin is not formed when heat treatment is performed in the next step, and the effect of improving the acid resistance of the substrate material consisting of a metal material or a resin material tends not to be obtained, which is undesirable. On the other hand, if the content of fluororesin in the composite plating film formed in step 4 exceeds 65% by mass, it becomes difficult to form the composite plating film by electroplating or electroless plating, which are relatively simple film formation methods, and this tends to lead to an increase in production costs, which is undesirable.

[0032] In this step 4, the method for forming the composite plating film containing a high concentration of fluororesin may be the same as that in the above-mentioned step 3. Specifically, for example, an electroplating solution consisting of an aqueous solution of nickel sulfamate tetrahydrate with a concentration of 200 g / L to 500 g / L, an aqueous solution of boric acid with a concentration of 40 g / L, and a dispersion of polytetrafluoroethylene resin with a concentration of 400 g / L to 800 g / L may be used, and a composite plating film consisting of fluororesin and nickel may be formed on the surface of the above-mentioned intermediate layer by electroplating while stirring with a stirrer at a speed of 2 cm / sec to 10 cm / sec. Here, if the composite plating film in this step 4 is formed on the surface of the intermediate layer without stirring, a homogeneous composite plating film with good reproducibility cannot be obtained due to partial precipitation of fluororesin particles, etc. As a result, when heat treatment is performed in the next step, an outermost layer consisting of fluororesin cannot be formed, and the effect of improving the acid resistance of the substrate material tends to be insufficient, which is not preferable.

[0033] Step 5: The substrate material with the composite plating film containing a high concentration of fluororesin is subjected to a heat treatment to form an outermost layer made of fluororesin.

[0034] In this step 5, a heat treatment is performed in air or in an inert gas atmosphere on the substrate material with the composite plating film containing a relatively high concentration of fluororesin formed in the above-mentioned step 4. As a result, a part of the fluororesin in the film is dissolved, and an outermost layer made of fluororesin is formed.

[0035] Here, the method and conditions for the heat treatment carried out in step 5 may be appropriately determined depending on the type of substrate material and fluororesin, etc. Specifically, for example, when the substrate material is any of copper, aluminum, iron, stainless steel, and polyimide resin, and the fluororesin is polytetrafluoroethylene (PTFE) resin or perfluoroalkoxyalkane (PFA) resin, the substrate material with the composite plating film containing a high concentration of fluororesin formed in the above step 4 may be placed in a commercially available heat treatment device, and heat treatment may be carried out in a nitrogen atmosphere at about 400°C to 450°C for about 10 to 20 minutes.

[0036] B. Substrate material with composite plating film, the outermost layer of which is fluororesin The invention of the present application relates to a substrate material with a composite plating film having an outermost layer of a fluororesin, which is formed by the above-mentioned method of forming a composite plating film having an outermost layer of a fluororesin according to the present application. The substrate material with a composite plating film having an outermost layer of a fluororesin according to the present application is characterized in that it does not show a corrosion potential with respect to the electrolytic solution when a corrosion potential measurement is performed using any one of hydrofluoric acid, sulfuric acid, and hydrochloric acid as the electrolytic solution. Therefore, according to the invention of the present application, it is possible to provide a substrate material made of a metal material or a resin material such as a polyimide resin, which has acid resistance and is not likely to corrode the surface even when it comes into contact with an acidic substance such as hydrofluoric acid, sulfuric acid, or hydrochloric acid.

[0037] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples. EXAMPLES

[0038] In this Example 1, a copper plate having a length of 20 mm, a width of 30 mm, and a thickness of 1 mm was prepared as a substrate material, and pretreatment was performed by the following method. First, the copper plate as the substrate material was immersed in an alkaline immersion degreasing bath (a mixed solution consisting of a sodium hydroxide aqueous solution having a concentration of 10 g / L, a sodium carbonate aqueous solution having a concentration of 50 g / L, a sodium orthosilicate aqueous solution having a concentration of 50 g / L, and a nonionic surfactant having a concentration of 1 g / L) at a liquid temperature of 50 ° C. for 10 minutes to degrease the surface, and then washed with pure water (ion-exchanged water). Next, the copper plate was immersed in an alkaline electrolytic degreasing bath (a mixed solution consisting of a sodium hydroxide aqueous solution having a concentration of 10 g / L, a sodium carbonate aqueous solution having a concentration of 50 g / L, a sodium orthosilicate aqueous solution having a concentration of 50 g / L, and a nonionic surfactant having a concentration of 1 g / L) at a current density of 6 A / dm 2 After electrolytic degreasing for 1 minute, the plate was rinsed with pure water. The plate was then immersed in a 10 wt% sulfuric acid solution at 25°C for 30 seconds to activate the surface, and then rinsed with pure water.

[0039] Next, the pretreated copper plate obtained by the above method was immersed in a Watts bath (an electroplating solution consisting of an aqueous solution of nickel sulfate hexahydrate with a concentration of 250 g / L, an aqueous solution of nickel chloride with a concentration of 50 g / L, and an aqueous solution of boric acid with a concentration of 40 g / L) at a liquid temperature of 50°C and pH 4.0, and the copper plate was used as the cathode and the nickel plate as the anode, with a current density of 3 A / dm 2 By performing electroplating treatment at 40° C. for 10 minutes, a nickel plating film with a thickness of 6 μm was formed as a base layer on the surface of the copper plate.

[0040] Next, the copper sheet with the nickel plating film was removed from the Watts bath, washed with pure water, and immersed in a composite plating bath (an electroplating solution consisting of an aqueous solution of nickel sulfamate tetrahydrate with a concentration of 720 g / L, an aqueous solution of boric acid with a concentration of 40 g / L, and a dispersion of polytetrafluoroethylene resin with a concentration of 100 g / L) with a liquid temperature of 40°C and pH of 4.0 to form a composite plating film containing a low concentration of fluororesin. The copper sheet was used as the cathode and the stainless steel sheet as the anode, and the current density was 1 A / dm 2A composite plating film (an intermediate layer consisting of fluororesin and nickel) containing low concentration polytetrafluoroethylene resin (fluororesin) was formed on the surface of the nickel plating film by performing an electroplating treatment at 400 K for 30 minutes. During the formation of the composite plating film, the composite plating bath placed in a container was stirred at 5 cm / sec using a stirrer.

[0041] Furthermore, the copper sheet with the composite plating film containing the low concentration of fluororesin was immersed in a composite plating bath (an electroplating solution consisting of an aqueous solution of nickel sulfamate tetrahydrate with a concentration of 180 g / L, an aqueous solution of boric acid with a concentration of 40 g / L, and a dispersion of polytetrafluoroethylene resin with a concentration of 500 g / L) with a liquid temperature of 40°C and pH of 4.0 for forming a composite plating film containing a high concentration of fluororesin, and the copper sheet was used as the cathode and the stainless steel sheet as the anode, and a current density of 1 A / dm 2 A composite plating film (a layer made of fluororesin and nickel) containing a high concentration of polytetrafluoroethylene resin (fluororesin) was formed on the surface of the intermediate layer by performing an electroplating treatment at 400° C. for 30 minutes. During the formation of the composite plating film, the composite plating bath placed in a container was stirred at 5 cm / sec using a stirrer.

[0042] Next, the copper plate with the composite plating film containing the high concentration of fluororesin was taken out of the composite plating bath and washed with pure water, and then the surface was dried using a commercially available air blower. The copper plate was placed in a commercially available heat treatment device and heat-treated at 420°C for 15 minutes in a nitrogen atmosphere to obtain a copper plate with a composite plating film whose outermost layer was made of fluororesin.

[0043] (Evaluation method) The surface of the copper plate with the composite plating film obtained in Example 1, the outermost layer of which was made of fluororesin, was observed with a FE-SEM (field emission scanning electron microscope). The results are shown in Figure 1 (A) and (B). Figure 1 (A), which shows a relatively low magnification, shows that the surface was free of defects such as cracks and had a generally flat shape. Figure 1 (B), which shows a relatively high magnification, shows that the surface was covered with fine protrusions and had a generally homogeneous shape.

[0044] Next, the corrosion potential measurement was performed on the copper plate with the composite plating film of which the outermost layer was made of fluororesin obtained in Example 1, using sulfuric acid of 98 wt% concentration as an electrolyte. The measurement conditions were as follows: the copper plate with the composite plating film of which the outermost layer was made of fluororesin obtained in Example 1 was used as the cathode, platinum was used as the anode, silver chloride was used as the reference electrode, and the scanning speed was 2 mV / sec. The result of this corrosion potential measurement is shown in FIG. 2. Here, FIG. 2 also shows the result of a corrosion potential measurement performed under the same conditions as in Example 1, using the same copper plate as in Example 1 as the cathode, as a comparison standard. In addition, the result of a corrosion potential measurement performed under the same conditions as in Example 1, using a nickel plate as the cathode, as a reference standard, is also shown.

[0045] As can be seen from the graph in FIG. 2, the current density value of the copper plate, which is the comparison standard, increased rapidly from a potential of about 0.10 V, and showed a clear corrosion potential against the sulfuric acid electrolyte. In addition, the current density value of the nickel plate, which is the reference standard, also increased gradually from a potential of about 0.03 V, and showed a clear corrosion potential against the sulfuric acid electrolyte. On the other hand, the current density value of the copper plate with a composite plating film whose outermost layer is made of fluororesin obtained in Example 1 hardly changed, and did not show a corrosion potential against the sulfuric acid electrolyte. Although not shown in FIG. 2, a nickel plate with a composite plating film whose outermost layer is made of fluororesin was formed under the same conditions as in Example 1 using a nickel plate as the substrate material, and the corrosion potential of the sample piece (nickel plate with a composite plating film whose outermost layer is made of fluororesin) was measured under the same conditions as in Example 1. The results were almost the same as those of the sample piece in Example 1 (copper plate with a composite plating film whose outermost layer is made of fluororesin). In conclusion, by forming a composite plating film with an outermost layer made of fluororesin on the surface of the copper plate, which is the substrate material, the corrosion of the copper plate caused by sulfuric acid, which is an acidic substance, was significantly suppressed. Therefore, it can be judged that the copper plate with the composite plating film with an outermost layer made of fluororesin obtained in Example 1 is not likely to be corroded on the surface even if it comes into contact with sulfuric acid, which is an acidic substance. [Industrial Applicability]

[0046] The invention of the present application can be suitably used as a method for imparting acid resistance to substrate materials made of metal materials or resin materials such as polyimide resin, so that the substrate materials are not corroded even when they come into contact with acidic substances such as hydrofluoric acid, sulfuric acid, hydrochloric acid, etc. The invention of the present application can also be suitably used for jigs and various devices used in semiconductor manufacturing processes, resin substrate materials used in the semiconductor field, etc.

Claims

1. A method for forming a composite plating film having an outermost layer made of a fluororesin for imparting acid resistance to a substrate material made of a metal or resin material, comprising the following steps 1 to 5: Step 1: The substrate material is subjected to pretreatment including degreasing and washing with water. Step 2: A metal plating film is formed on the pretreated substrate material. Step 3: A composite plating film containing a low concentration of fluororesin is formed on the substrate material with the metal plating film while the plating bath is stirred. Step 4: A composite plating film containing a high concentration of fluororesin is formed on the substrate material with the composite plating film containing a low concentration of fluororesin while stirring the plating bath. Step 5: The substrate material with the composite plating film containing a high concentration of fluororesin is subjected to a heat treatment to form an outermost layer made of fluororesin.

2. 2. The method for forming a composite plating film having an outermost layer made of a fluororesin according to claim 1, wherein the substrate material is any one of copper, aluminum, iron, stainless steel, and polyimide resin.

3. 3. The method for forming a composite plating film having an outermost layer made of a fluororesin according to claim 1, wherein the fluororesin is a polytetrafluoroethylene resin or a perfluoroalkoxyalkane resin.

4. 2. The method for forming a composite plating film having an outermost layer made of a fluororesin according to claim 1, wherein the metal plating film formed in step 2 is made of nickel or a nickel alloy.

5. 2. The method for forming a composite plating film having an outermost layer made of a fluororesin according to claim 1, wherein the composite plating film formed in step 3 contains 5% by mass to 25% by mass of a fluororesin.

6. 2. The method for forming a composite plating film having an outermost layer made of a fluororesin according to claim 1, wherein the composite plating film formed in step 4 contains 30% by mass to 65% by mass of a fluororesin.

7. A substrate material having a composite plating film, the outermost layer of which is a fluororesin, formed by the method for forming a composite plating film, the outermost layer of which is a fluororesin, according to claim 1, A substrate material with a composite plating film, the outermost layer of which is a fluororesin, characterized in that when a corrosion potential measurement is performed using any one of hydrofluoric acid, sulfuric acid, and hydrochloric acid as an electrolyte, the substrate material exhibits no corrosion potential in the electrolyte.

Citation Information

Patent Citations

  • Plated formed body and its production

    JP1999217691A